Do cotidiano ao artifício : estratégias para produção de emoção em filmes da nova geração do cinema de horror nacional - Fonseca, Sâmia Lorena Morais da (2017)
The following dissertation is devoted to the new horror movies produced in Brazil after 2000’s. Special attention will be given to their affective dimension, focusing on the relation between the emotional expression of its characters and the spectators reaction. Among typical strategies programmed in these films, we find a distinct process of artificialization of daily life, through the deliberate use of conventions proper to the horror genre. The films will be approached through a a cognitive perspective, developed in film studies from the 90s. In order to analyze each film, we will depart from the methodological perspective of the Film Poetics, according to which a cinematographic work is an expressive composition that causes effects in the spectator. Four films were analyzed, (one feature film and three short films): Quando eu era vivo (2014), Vinil Verde (2004), O Duplo (2012) and Estátua (2014).